Stochastic multistep polarization switching in ferroelectrics - Genenko, Y.A.; Khachaturyan, R.; Schultheiß, J.; Ossipov, A.; Daniels, J.E.; Koruza, J. (American Physical Society, 2018)
Consecutive stochastic 90° polarization switching events, clearly resolved in recent experiments, are described by a nucleation and growth multistep model. It extends the classical Kolmogorov-Avrami-Ishibashi approach and includes possible consecutive 90°- and parallel 180° switching events. The model predicts the results of simultaneous time-resolved macroscopic measurements of polarization and strain, performed on a tetragonal Pb(Zr,Ti)O3 ceramic in a wide range of electric fields over a time domain of seven orders of magnitude. It allows the determination of the fractions of individual switching processes, their characteristic switching times, activation fields, and respective Avrami indices.